Plotting the Palestinian Nakba: Family and Identity Displacement in Abulhawa’s Mornings in Jenin - Nassima BENATTIA, Samah BOUMAKHLOUF (My University, 2020)
Susan Abulhawa made a great contribution to Arab-American literary creativity in the English language through her novel Mornings in Jenin, which exhibits the plight of a Palestinian family across four generations in refugee camps and in exile from 1948 to 2006, the year the novel was published. Accordingly, this thesis sets out to study the relationship between post-war trauma and the Palestinian identity in the selected narrative by examining the way misery and displacement affect individual Psyche and destruct identity. The present study also inspects the main characters’ efforts to break free from the hardship resulted from war in Palestine and loss in exile. To this end, this dissertation is divided into two chapters; the first one seeks to study the ethnic, religious, and national identity of Palestine by identifying its historical roots and literary theories related to the colonial and Diaspora discourses to provide a better view of the second chapter. The latter, in its turn, investigates the stylistic and thematic issues related to trauma and its influence on family structure, and identity deconstruction. It highlights, through psychoanalytic and post-colonial theories, the characters’ struggling to reformulate individual and collective identity employing several techniques such as dialogue, silence, practice, interaction, memory, history, resistance, and resilience.
Keywords: Key words: Individual/ collective identity, identity deconstruction / reconstruction, Diaspora, colonial discourse, post-war trauma.